Machine Learning- Individual Models verses Ensemble Models on Suicidal Rate - Nethravathy, K.; Saraswathi, D. (International Journal of Psychosocial Rehabilitation, 2020)
Sentimental analysis through Machine Learning is a wide area of research in the field of social media. The most popular and universally used social media like twitter helps in gathering the data in all the field of research. The word sentimental points to a very specific feature in the dataset that has to be selected for further analysis. The opinions, thoughts or feelings of the society about one particular topic like suicide/movie/new product can be received by twitter. The different Machine Learning algorithms like Random Forest, Linear Regression can be considered to check the accuracy. On the other hand the ensemble methods such as Bagging, Boosting and voting can also be applied on the dataset. Hence, individual algorithm and the ensemble methods used are analyzed to estimate most suitable Machine Learning Model The good model gives more accuracy result when applied on realistic life.